Potent inhibition of miR-27a by neomycin–bisbenzimidazole conjugates1. Issue 10 (14th October 2015) - Nahar, Smita; Ranjan, Nihar; Ray, Arjun; Arya, Dev P.; Maiti, Souvik
<x xml:space="preserve">Abstract</x> Potent downregulation of oncogenic miRNA is obtained by conjugation of neomycin and bisbenzimidazoles.